A Comparative Analysis of the Productivity of Islamic and Conventional Mutual Funds in Indonesia: Data Envelopment Analysis (DEA) and General Least Square (GLS) Approaches - Abd. Majid, M. Shabri; Maulana, Hartomi (Gadjah Mada International Journal of Business, 2012)
This paper is an extended version of our earlier study (Abd. Majid and Maulana 2010) to further re-examine the relative efficiencies of selected Islamic and conventional mutual funds companies in Indonesia during the period 2004 to 2007 and their determinants. To measure their efficiencies, the output-input data consisting of a panel of conventional and Islamic mutual funds companies are empirically examined based on the most commonly used non-parametric approach, namely, Data Envelopment Analysis (DEA). It also attempts to investigate the influence of the mutual funds companiesâ characteristicson efficiency measures using the Generalized Least Square (GLS) estimation. The study finds that, on average, the Indonesian mutual funds companies experienced a decrease in Total Factor Productivity (TFP) growth. It is mainly caused by a decline in both efficiency and technical efficiencies, where the efficiency change is largely contributed by the changes in pure efficiency rather than scale efficiency. Additionally, the study also documents that the funds size negatively affects efficiency. This indicates that due to its diseconomies of scale, a larger mutual funds company is less efficient than a smaller funds company. Finally, in comparing the efficiency of the mutual funds companies, the study finds that, on average, the Islamic unit trust companies perform more poorly than their conventionalcounterparts.